2014
DOI: 10.1002/rcm.6902
|View full text |Cite
|
Sign up to set email alerts
|

The application of a new microfluidic device for the simultaneous identification and quantitation of midazolam metabolites obtained from a single micro‐litre of chimeric mice blood

Abstract: Improvements in the enhanced ionisation efficiency from the microfluidic device in conjunction with nanoUHPLC/MS was sufficiently sensitive for the identification and quantification of midazolam metabolites from a single micro-litre of whole blood. Detection of metabolites not previously recorded from the chimeric mouse in vivo model was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Recently Gallagher et al showed that a prototype microfluidic chip-based device coupled with HRMS could be utilized for the identification and quantification of midazolam and associated metabolites in 1 μl samples of mouse blood from control and humanized chimeric mice. The enhanced sensitivity of the method allowed the metabolites that had previously not been observed in samples from chimeric mice to be detected [108].…”
Section: Application Of Integrated Microfluidic (Chipbased) Lc-ms Formentioning
confidence: 98%
See 1 more Smart Citation
“…Recently Gallagher et al showed that a prototype microfluidic chip-based device coupled with HRMS could be utilized for the identification and quantification of midazolam and associated metabolites in 1 μl samples of mouse blood from control and humanized chimeric mice. The enhanced sensitivity of the method allowed the metabolites that had previously not been observed in samples from chimeric mice to be detected [108].…”
Section: Application Of Integrated Microfluidic (Chipbased) Lc-ms Formentioning
confidence: 98%
“…The application of integrated microfluidic LC or (chipbased LC) with MS for the analysis of biofluid samples has been well documented for the analysis of many different compound classes in biofluids including: glycans, various lipid classes, small molecule drugs, peptides and proteins [83,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108]. To date the vast majority of examples of chip-based LC-MS quantification of analytes in biofluids has been carried out using low-resolution mass spectrometers such as tandem quadrupole MS.…”
Section: Application Of Integrated Microfluidic (Chipbased) Lc-ms Formentioning
confidence: 99%
“…High‐performance liquid chromatography (HPLC) coupled to mass spectrometry (MS) is currently the method of choice for metabolite identification and quantification studies for small molecules, peptides and others 1–7 . Improvements in chromatographic separation such as ultra‐high‐performance liquid chromatography (UPLC) have generally led to higher chromatographic resolution, 8 with sharper peaks and correspondingly higher MS sensitivity 9 . A common strategy for MS data acquisition involves data‐dependent acquisition (DDA) in which a list of likely metabolites is employed to drive targeted fragmentation (MS 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nano-LC and μLC systems have been developed by several vendors and are quickly gaining popularity. One of these is an integrated μLC-electrospray chip MS interface introduced in 2014, the Waters IonKey/MS™ [16,17]. Applications range from steroids and midazolam to peptides [16,[18][19][20].…”
mentioning
confidence: 99%